Patients Outcome with Brain Oligometastases Treated with the SIB-IMRT Technique: Dr. Kariadi General Hospital Experience - Christina Hari Nawangsih; Harman Juniardi; Dion Firli; Sigit Wirawan; Sri Rahayu Subandini; Diaza Okadimar Ariyanto (Radioterapi & Onkologi Indonesia, 2022)
Brain metastases are often considered as the end of life in oncologic diseases. Previously, a standalone Whole Brain Radiotherapy (WBRT) had been the standard of care in the case of single or multiple lesions. Currently, Simultaneous Integrated Boost - Intensity Modulated Radiotherapy (SIB-IMRT) permits the delivery of simultaneous doses within a single therapy to the whole brain and the local lesion, therefore shifting the care expectation from palliative towards curative. This study summarizes the outcome in cancer patients with brain oligometastases that were treated with the SIB-IMRT technique. Between April 2020 and April 2021, a total of 29 brain oligometastases patients were treated with the SIB-IMRT technique at Dr. Kariadi General Hospital. Twenty patients completed treatment with a whole-brain dose of 37.5 Gy and tumor dose of 45 Gy, both in 15 fractions. Among fifteen who were successfully followed-up, six at the 6th-month follow-up, complete data of four patients were included. All four patients improved clinically. Evaluation from imaging revealed mass reductions in two patients, while one patient’s metastases were progressing, and the other one showed no changes. Additionally, no patients demonstrated cerebral necrosis as a late side effect.